Pilot Study on the Diagnostic Performance of a Portable Non-Mydriatic Retinal Camera for the Diabetic Retinopathy Diagnosis in Type 2 Diabetic Patients in Medellín, Antioquia - Martínez Rua, Alexander; Llano Naranjo, Yenny; Gaviria Jimenez, Juan José; Llano Naranjo, Yuliana; Sucerquia Giraldo, Juan Alejandro; Patiño Giraldo, Santiago (Iatreia, 2025)
Introduction: Portable retinal cameras represent a potentially valuable tool in teleophthalmology to facilitate the diagnosis of diabetic retinopathy. Objective: To evaluate the diagnostic sensitivity and specificity of a portable non-mydriatic retinal camera in diagnosing diabetic retinopathy compared to fundoscopic examination by an ophthalmologist. Methodology: A cross-sectional study was conducted in a population over 18 years of age diagnosed with type 2 diabetes mellitus. Fundus images were obtained using the NIDEK Versacam® camera and compared with fundoscopic examination performed by an ophthalmologist. Sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratios (LR) were calculated with their respective 95% confidence intervals based on interpretations by three different evaluators according to the American Academy of Ophthalmology classification. Results: Between October and November 2018, 91 images from 81 patients were obtained. Image quality was graded according to clarity classification by three independent evaluators. The analysis yielded a sensitivity of 30% and specificity of 80%. Images were classified as excellent in 10.4% of cases (8-13/91), good in 10.5% (8-12/91), acceptable in 20% (17-19/91), and inadequate in 58% (49-56/91). Conclusions: Screening for diabetic retinopathy using a portable non-mydriatic retinal camera in type 2 diabetes mellitus patients yields a high number of inadequate photographs and demonstrates sensitivity below recommended standards.